Education and happiness in the school-to-work transition - Dockery, A.M. (My University, 2010)
Very few would argue that education does not enhance people’s lives, with higher educational attainment being linked to better career paths and health. It is curious then that previous research has found that attaining higher levels of education is linked to lower levels of happiness or satisfaction with life. This would appear to be at odds with current policy promoting the value of further education. Could it be that attaining higher education sets people up to fail by encouraging expectations that can never be met? Using data from the 1995 Year 9 cohort of the Longitudinal Surveys of Australian Youth (LSAY), Mike Dockery examined the relationship between individuals’ highest level of education and their selfrated happiness. He also looked at the impact of factors such as family circumstances while at school and personality traits on this relationship
Longitudinal Study of Australian Youth
Keywords: Employment; Education and Training; Learning, education and training; Labour market; Education and Training; Employment; Learning, education and training; Employment and unemployment